Estrutura econômica e distribuição interpessoal de renda no nordeste - Soares, Fernanda Braga (2012)
Despite the inequality in income distribution of the Brazilian population come down over time, Brazil also has one of the worst income distributions in the world, especially when taking into account other countries with similar levels of development. In this context, is the Northeast, which has the highest income inequality and where the concentration of income has been falling more slowly compared to the rest of Brazil. An improvement exacerbated indicators such as poverty and income distribution may be related to economic structure, so that not all sections of the population to benefit from the fruits produced by an increase in income or economic growth. That is, trade flows, the sectoral structure of employment and production, the technology standard, the structure of consumption, and others may influence the effects caused by changes in the economy on indicators such as inequality. Accordingly, this study aims to assess how the economic structure of the Northeast region influences the effects of changes in the local economy on inequality, using the model of Leontief-Miyazawa. For this, were used information contained in the input-output matrix of the Northeast for the year 2004, the primary data of the Survey by Household Sampling - PNAD 2004, addition to the data from the Household Budget Survey - POF, using the structure of POF 2002/2003. Through simulations of impacts in each sector of economic activity was obtained the distribution of income provided for that impact and, consequently, the sectors responsible for the increase or reduction of inequality. Through the results it was found that only nine sectors improved the Gini index and the sectors with the greatest weight in the consumption of the poorest families contributed to a greater concentration of income after the impact. Moreover, was made an analysis of the effects of changes in production structure in the Northeast between 1997 and 2004 about the income distribution. For this, we used data from the input-output matrix of the Northeast in 1997 and household income data obtained by PNAD, referring to the same year. The results indicate that the lower income classes generate more income in the economy as a whole and absorb less. Finally, it was observed that changes in the productive structure occurred between 1997 and 2004 helped to improve the income distribution in the Northeast.